BIOKLIMATIK BUILDING OF MICE AT LASWI BANDUNG - khafid, aqidon noor (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2024)
CAPITAL DRIVEN ARCHITECTURE Indonesia is a country with a developing economy. We can see the progress of a country from the architectural works in it. Architecture is a product of capitalism, meaning architecture that is driven by capital. If we talk about architecture, it is very much related to commerce, which some consider taboo, when it comes to money. In fact, without money, architecture cannot be built!WHAT COMES NEXT? ARCHITECTURE THAT SUITS THE ECONOMIC CONTEXT?Why don't we make an example of a Bioclimatic concept MICE building, because the average MICE building in Indonesia is formal? we make SOMETHING UNIQUE, DIFFERENT, VERY BIOCLIMATIC and energy efficientWHAT DOES THIS HAVE TO DO WITH BIOCLIMATICS?The Bioclimatic MICE concept is one of the design approaches chosen, namely sustainability and dialogue with the climate. So this building will use as little artificial energy as possible so that it will have a big impact on the capital for this building.FUTURE BIOCLIMATIC DESIGN?Buildings have a value that will decrease, but that depends on the experimental design of this building. Already thinking about future design inflation.